Optimal utilization of ecological economic resources and low-carbon economic analysis from the perspective of Public Health - Wang, Qi; Feng, Yan; Hu, Ao (Frontiers in Public Health, 2023)
China’s urbanization process continues to deepen with social development, but the optimal utilization of ecological, economic resources and Public Health (PH) problems are becoming increasingly severe. This paper analyses the optimal use of urban resources based on PH. Here, the public space of urban settlements is selected as the research object. Firstly, the connotation and essence of the ecological economy and Low-Carbon Economy (LCE) are analyzed. Secondly, the characteristics of public space in urban settlements are studied based on PH. The public space satisfaction evaluation model in urban settlements is constructed with 5 first-level and 12 second-level indicators. Finally, a questionnaire is designed to analyze urban households' outdoor activities and evaluate public space in settlements. The influencing factors of residents’ satisfaction with public space in settlements are obtained through regression analysis. The results show that residents’ satisfaction with the public space of the settlement is mainly evaluated from three aspects: the accessibility of public space, the integrity of public space, and the pleasure of public space. The influence coefficients are 0.355, 0.346, and 0.223, respectively, indicating that the influence degree of the three principal factors decreases. This paper on the satisfaction of public space in urban settlements from the perspective of PH can provide a reference for the optimal utilization of public space resources under the current ecological economy and LCE.